THE ROLE OF GREENPEACE INDONESIA IN ENCOURAGING THE JAKARTA PROVINCIAL GOVERNMENT TO ADDRESS AIR POLLUTION (2021–2023) - Shafiyah Kirana Putri; Muharjono, Muharjono (Jurnal Paradigma, 2025)
ABSTRACTAir pollution in Jakarta during the 2021–2023 period became an urgent environmental issue due toits direct impact on public health. In this context, Greenpeace Indonesia actively pushed theProvincial Government of DKI Jakarta to become more responsive, despite the absence of anyformal cooperation agreement. This study aims to analyze the advocacy and campaign strategiesused by Greenpeace Indonesia to influence public policy on air pollution control. Using aqualitative descriptive approach and Clive Archer’s theory of International Organizations, thisresearch explores the interaction between Greenpeace Indonesia and the DKI Jakarta Governmentas non-state and state actors in the international system. The findings show that through digitalcampaigns, community engagement, and collaboration with academics and media, GreenpeaceIndonesia effectively raised public awareness and exerted moral-political pressure on the DKIJakarta Government. These findings affirm the vital role of civil society organizations in shapingenvironmental policy responses, particularly when formal mechanisms are absent.Keywords: Greenpeace Indonesia, air pollution, advocacy, DKI Government